Deposition and characterization of AZO thin films on flexible glass substrates using DC magnetron sputtering technique. Issue 5 (1st April 2017) - Xia, Yanping; Wang, Peihong; Shi, Shiwei; Zhang, Miao; He, Gang; Lv, Jianguo; Sun, Zhaoqi
Abstract: Al-doped zinc oxide (AZO) thin films were deposited onto flexible ultra-thin glass substrates by using a direct current (DC) magnetron sputtering process. The effects of sputtering power, working pressure and substrate temperature on the morphology and optoelectronic performances of AZO films were investigated. The optimal sputtering power, working pressure and substrate temperature for AZO film were determined to be 100 W, 0.9 Pa and 150 ℃, respectively. Further increasing or decreasing the sputtering power, working pressure and substrate temperature degrades the quality of AZO films. XRD patterns show all as-sputtered AZO thin films are preferred to grow along <0002> direction. Moreover, the largest grain size, which depicts the best microstructure of AZO films, matches with the smallest stress value. It can be seen from SEM images that the surface is smooth and dense. The smallest value of the resistivity is 1.784×10 −3  Ω cm and the average transmittance of all AZO films in the visible range is about 80%. The X-ray photoelectron spectroscopy spectra show that the amount of Al element in the AZO film is very small.